Upaya Badan Penanggulangan Bencana Daerah (BPBD) dalam penanggulangan bencana banjir - Ahmad Udori; Miranti Miranti (Universitas Muara Bungo, 2019)
From the results of the author's research entitled Performance of the Regional Disaster Management Agency in Flood Disaster Management in Tebo Regency (Case Study of BPBD in Tebo Regency) as follows: Government Efforts of the Regional Disaster Management Agency in tackling Floods. Socialization Preparing for flooding This socialization was carried out for the people of the Tebo Regency Government to better know how to deal with flooding in the village. So that when the flood disaster comes the people are not surprised. Post Flood Action One of the impacts of the disaster on the declining quality of life of the population can be seen from various public health problems that occur. Disasters that are followed by displacement have the potential to cause health problems that are actually preceded by problems in other fields/sectors. Constraints faced by the government of the Tebo Regency Government in overcoming the flood disaster in Tebo Regency. Lack of funds. Funds are used in socialization activities carried out by the Government of Tebo Regency, especially BPBD KAbebo District. Because in this socialization activity requires presenters and consumption for guests and the community. But the Tebo Regency Government lacked funds in this matter. Lack of community awareness. The lack of awareness here means that in the socialization activities carried out by the Tebo Regency Government, not many people attend. Though in this socialization do is for their own interests. Not many people realize that this is important.AbstrakArtikel ini bertujuan untuk melihat upaya yang dilakukan oleh stakeholder tertentu dalam menangani bencana banjir. Banjir adalah ancaman musiman yang terjadi apabila meluapnya tubuh air dari saluran yang ada dan menggenangi wilayah sekitarnya. Banjir merupakan ancaman alam yang paling sering terjadi dan banyak merugikan. Sungai-sungai di Indonesia 30 tahun terakhir ini mengalami peningkatan termasuk di daerah Kabupaten Tebo. Penelitian ini menggunakan pendekatan metode deskriptif kualitatif. Lokasi penelitian ini dilakukan di Instansi Badan Penanggulangan Bencana Daerah Kabupaten Tebo. Sosialisasi Pesiapan menghadapi banjir Sosialisasi ini dilakukan untuk masyarakat Pemerintah Kabupaten Tebo supaya lebih tahu bagaimana persiapan mengahadapi banjir di kelurahan tesebut. Supaya disaat bencana banjir datang masyarakat tidak terkejut. Tindakan Pasca Banjir Salah satu dampak bencana terhadap menurunnya kualitas hidup penduduk dapat dilihat dari berbagai permasalahan kesehatan masyarakat yang terjadi. Kendala yang di hadapi pemerintah Pemerintah Kabupaten Tebo dalam menanggulangi Bencna banjir di Kabupaten Tebo. Kekurangan Dana. Dana digunakan dalam kegiatan sosialisasi yang dilakukan oleh Pemerintah Kabupaten Tebo Khususnya BPBD Kabupaten Tebo. Karena dalam kegiatan sosialisasi ini membutuhkan pemateri dan konsumsi untuk tamu dan masyarakat. Namun pihak Pemerintah Kabupaten Tebo kekurangan dana dalam hal ini. Kurang kesadaran Masyrakat. Kurangnya kesadaran disini maksudnya adalah dalam kegiatan sosialisasi yang dilakukan Pihak Pemerintah Kabupaten Tebo masyarakat tidak banyak yang menghadiri.